Time and department distribution of hypoglycemia occurrences in hospitalized diabetic patients - Cun-mei Yang; Yan-lan Ma; Jun Kang; Zhe Jia; Yan-yan Wang; Hong-ying Ma; Jie Wang (Elsevier, 2015)
Hypoglycemia occurred on hospitalized patients would result in severe complications. So we monitored the blood glucose of hospitalized patients with diabetes in 14 clinical departments from January to December 2013. Totally 105728 cases of blood glucose were monitored and 1374 cases of hypoglycemia were detected. The incidence of hypoglycemia was 1.29%. Among which, 317 cases of severe hypoglycemia were detected and the incidence of severe hypoglycemia was 0.29%. The peak periods of hypoglycemia were 0:00∼2:00, 22:00∼24:00, 2:00∼4:00, 8:00∼10:00 and 10:00∼12:00.The symptomatic hypoglycemia accounted for 47.01%, The asymptomatic hypoglycemia accounted for 52.98%. The incidence of hypoglycemia was 1.49% in medical departments and 0.87% in surgical departments. It is suggested to be vigilant of high risk periods of hypoglycemia, detect and treat asymptomatic hypoglycemia timely and rationally administer antidiabetics to prevent hypoglycemia.